(untitled) (Medicine Today, 2013)
Hypothyroidism is an important metabolic disorder and is associated with many biochemical abnormalities. Many studies were done regarding the biochemical status of hypothyroid patients including lipid profile. But controversies still prevail. So, a cross sectional study was done in our population to evaluate lipid profile status of hypothyroid patients compared to age and sex matched healthy euthyroid persons. In our study mean serum total cholesterol, LDL cholesterol and triacylglycerol levels in cases and controls were 241.56 ± 60.05 vs 146.94 ± 23.21 mg/dL, 151.96 ± 59.60 vs 71.43 ± 26.83 mg/dL and 212 ± 100.73 vs 98.87 ± 39.69 mg/dL respectively with p values < 0.001 whereas HDL cholesterol was found significantly decreased in cases compared to controls (49.59 ± 11.69 vs 55.89 ± 11.70 mg/dL with p value < 0.05). Results of our study suggest that dyslipidemias are associated with hypothyroidism. Therefore, patients presenting with dyslipidemia are recommended for investigation to explore hypothyroidism DOI: http://dx.doi.org/10.3329/medtoday.v25i1.15904 Medicine Today 2013 Vol.25(1): 21-24